2013
DOI: 10.1080/17408989.2013.837438
|View full text |Cite
|
Sign up to set email alerts
|

Toward an understanding of the democratic reconceptualization of physical education teacher education in post-military Brazil

Abstract: , M. A. (2015). Toward an understanding of the democratic reconceptualization of physical education teacher education in post-military Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A final group of studies referred to the experiences and views of participants in socio-critical interventions (Brooker and MacDonald, 1999; Bruce, 2013; Cameron, 2012; Da Matta et al, 2015; Devís-Devís and Sparkes, 1999; Muros and Fernández-Balboa, 2005; Sicilia-Camacho and Fernández-Balboa, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A final group of studies referred to the experiences and views of participants in socio-critical interventions (Brooker and MacDonald, 1999; Bruce, 2013; Cameron, 2012; Da Matta et al, 2015; Devís-Devís and Sparkes, 1999; Muros and Fernández-Balboa, 2005; Sicilia-Camacho and Fernández-Balboa, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the papers selected took an introspective approach, in which the authors analysed themselves. First of all, Da Matta et al’s (2015) study used a retrospective analysis of a student’s personal experiences to establish the evolution of PE and PETE as a result of the fall of the Brazilian military dictatorship. The conclusions from this article suggested that students’ experiences, in general, had a major impact on their conceptions of PE and in the consolidation of a personal democratic view of education.…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis was conducted by the second and third authors through an amalgamation of an inductive and deductive approach. We intentionally included this outsider perspectives to balance and account for the first author bias, given his role of teacher educator and researcher (Da Matta, Richards, & Hemphill, 2015). From the cross-pattern text analysis the most coinciding excerpts were codified in the initially (Saldaña, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Over time, critics of the dominant authoritarian model of schooling have called for an extensive transformation that promotes learner-centered and democratic pedagogies (Harber, 2009), with reforms aimed at encouraging democratic practices and empowering learners through education. However, such reforms might not be possible without simultaneously changing the processes followed in teacher education programmes (Apple, 2001;DaMatta et al, 2013).…”
Section: Undemocratic Practicesmentioning
confidence: 99%